A Semiotic Analysis of IKEA’s Visual Metaphors: Exploring the Symbolic Language of Advertising - Almaghribi, Iflichul Arif; Himmawati, Dian Rivia (English Department, Universitas Negeri Surabaya, 2024)
IKEA tend to uses creative and innovative way in advertising to attract the audience’s attention, such as visual metaphor. Even though it is unique and interesting, this advertisement requires a slogan as a textual element to convey its message. This study aims to identify the meanings and the types of the visual metaphor in the advertisements. It uses qualitative method which the subjects are the utterances of selected IKEA visual metaphor advertisements by using documentation from the internet as the data collection technique. The result of this study is the types of visual metaphor that mostly occur are fusion, which has a more favorable influence in the context of advertising compared to other forms of visual metaphor. Furthermore, researcher found that visual metaphor is simply a visualization of figure of speech that can be utilized as marketing strategy because it has probabilities in visual communication such as attracts audiences’ attention, leaves a lasting impact, gives a positive attitude towards the advertisement, makes the sense of curiosity, and increases company’s reputation.